(untitled) (Asian Education Studies, 2016)
People are expected to carry out certain roles and duties throughout their lives in a society. The inability of people to carry out their roles and duties in a society due to various factors is defined as “disability.” Considering that there are 1,559,222 disabled individuals in our country, the rate holds an important place within the general population. Each individual is either disabled, has a disabled relative or a candidate for disability. Thus it is necessary to provide suitable conditions to enable disabled individuals live in concert with the society. This study is conducted in order to determine the level of influence of a 28-hour sport and game activity each week, for 14 weeks, on autistic individuals who have weak socializing and communications skills. This research is conducted on 2 male autistic children of a volunteer family during the fall semester of 2014-2015 academic year; this research also includes preliminary test and proof positive through face to face interview with the family. Descriptive analysis and content analysis are used in data analysis. All of the procedures are carried out by qualitative analysis program NVIVO 10. The names of disabled individuals who attended the research are undisclosed. In the end of this research, the statements released during the interviews show that physical education and game activities have an important influence on the development of disabled individuals. In this respect, the statements given at the end of the research are presented as Emotions and Thoughts of the Mother and Emotions and Behaviors of the Children.